Potential Role of Quercetin Glycosides as Anti-Atherosclerotic Food-Derived Factors for Human Health - Junji Terao (Antioxidants, 2023)
Quercetin is a monomeric polyphenol of plant origin that belongs to the flavonol-type flavonoid subclass. Extensive studies using cultured cells and experimental model animals have demonstrated the anti-atherosclerotic effects of dietary quercetin in relation to the prevention of cardiovascular disease (CVD). As quercetin is exclusively present in plant-based foods in the form of glycosides, this review focuses on the bioavailability and bioefficacy of quercetin glycosides in relation to vascular health effects. Some glucose-bound glycosides are absorbed from the small intestine after glucuronide/sulfate conjugation. Both conjugated metabolites and deconjugated quercetin aglycones formed by plasma β-glucuronidase activity act as food-derived anti-atherogenic factors by exerting antioxidant, anti-inflammatory, and plasma low-density lipoprotein cholesterol-lowering effects. However, most quercetin glycosides reach the large intestine, where they are subject to gut microbiota-dependent catabolism resulting in deglycosylated aglycone and chain-scission products. These catabolites also affect vascular health after transfer into the circulation. Furthermore, quercetin glycosides may improve gut microbiota profiles. A variety of human cohort studies and intervention studies support the idea that the intake of quercetin glycoside-rich plant foods such as onion helps to prevent CVD. Thus, quercetin glycoside-rich foods offer potential benefits in terms of cardiovascular health and possible clinical applications.